PERSEPSISUKUDAYAKKALISTERHADAPKEARIFANLOKAL SIPAUTANGDIDESARANTAUKALISKABUPATEN KAPUASHULU - Kristina Subek; Yohanes Bahari; Stella Prancisca (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis article is entitled " Perception Of The Dayak Kalis Tribe On Local Wisdom Sipautang In Kalis Rantau Village Kapuas Hulu". The problem in this study is how the Kalis Dayak people perceive the local wisdom of Sipautang in Rantau Kalis Village, Kalis District, Kapuas Hulu Regency. The purpose of the study was to determine the perception of the Kalis Dayak Tribe towards the process of implementing Sipautang local wisdom, the results of the traditional decisions of Sipautang local wisdom, and the existence of Sipautang local wisdom in Rantau Kalis Village, Kapuas Hulu Regency. This study uses a quantitative descriptive approach. The number of samples taken is 221 according to the number of samples of Isaac and Michael. The method used is Nonprobability Sampling. Data collection techniques with direct communication techniques, indirect communication, and documentary. The result of the research is that people know the process of implementing local wisdom Sipautang obtained 41.51%. The traditional decision in Sipautang local wisdom is 45.92% of the people accept the results of the Sipautang local wisdom customary decision and the perception of the Kalis Dayak tribe on the existence of Sipautang local wisdom is 36.42%.Keywords: Dayak, Local Wisdom, Ritual